Analisis Sistem Informasi Akuntansi dan Pengendalian Internal Terhadap Kinerja Perusahaan Studi PT. Petrokopindo Cipta Selaras - Afif, Mochammad Ilham; Suwandi, Suwandi (Universitas Muhammadiyah Gresik, 2023)
This study examines the effect of accounting information systems and internal control on company performance. Based on the perspective of contingency theory used in accounting systems is based on a premise that no accounting system is universally always appropriate to be applied to the entire organization in every circumstance, but the accounting system also depends on situational factors that exist in the organization. This study used a sample of companies at PT. Petrokopindo cipta aligned. The method used in finding samples is the porposive sampling technique. The results showed that accounting information systems and internal control had a significant effect on company performance.